Fracture simulation of concrete beams to assess softening behavior by varying different fractions of aggregates - H. S. Vishwanatha; S. Muralidhara; B. K. Raghu Prasad (Fracture and Structural Integrity)
Simulating the concrete fracture unlike other elastic and brittle materials quite different due to its quasibrittleness. The present research focussed on assess softening behavior by varying different fractions of aggregates and cement matrix in micro details. Extended Finite Element Method (XFEM) for crack modeling implemented for simulating and visualizing crack propagation through Cement matrix, Interfacial Transition Zone (ITZ) and Aggregates . This approach permits the initializing crack by from enrichment zone and propagation of crack through element by traction separation law .The crack formation initiates when the maximum principal tensile stress reaches the tensile strength. The work involves creating python script for iterative process of random distribution of aggregates with in the matrix using Monte Carlo method and creating Cohesive zone element for zero thickness ITZ. introduces a finite element modeling technique for investigating multiscale fracture characteristics. This approach encompasses multiple levels of analysis, including the generation of aggregate particles using a Monte Carlo method implemented via a Python script. Additionally, we replicate the Interfacial Transition Zone (ITZ) between aggregate and mortar in the model. The load-deflection curves can be used to assess the softening behavior of concrete and suggest the realistic fraction of coarse aggregate in mix proportion to impart more ductility to beams.